2017
DOI: 10.1016/j.sapharm.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacy led medicine reconciliation at hospital: A systematic review of effects and costs

Abstract: 1Background: Transition of patients care between settings presents an increased opportunity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 37 publications
0
44
1
Order By: Relevance
“…Hammad et al ,22 in their systematic review of studies of ‘complete MR’ (on admission and through to discharge) also found scant published evidence of the cost-effectiveness of pharmacy-led MR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hammad et al ,22 in their systematic review of studies of ‘complete MR’ (on admission and through to discharge) also found scant published evidence of the cost-effectiveness of pharmacy-led MR.…”
Section: Discussionmentioning
confidence: 99%
“…At 6 months postdischarge, the savings in medication costs outweighed staff costs. A systematic review of effects and costs of pharmacy-led MR22 could not come to a definite conclusion on the effects and costs. Both studies combined admission and discharge MR.…”
Section: Introductionmentioning
confidence: 97%
“…There is currently a recognised lack of evidence supporting the cost-effectiveness of MR interventions provided by pharmacists 16. A model built in 2008 to estimate the likely cost-effectiveness of preventing medication error at hospital admission using MR suggested that a pharmacist-based intervention is likely to be cost-effective but was based solely on US error data and made assumptions concerning the severity of errors prevented 17…”
Section: Introductionmentioning
confidence: 99%
“…The risk of adverse drug events increases with insufficient pharmacological knowledge of healthcare professionals, documentation errors in patient records and limited pharmacy service in the clinic . To mitigate this, clinical pharmacy services targeting different situations in the hospital setting have been developed and evaluated during the last decades .…”
mentioning
confidence: 99%